Robust H∞ infinity control for generalized network control systems with long time delay - Liyun YANG (Journal of Hebei University of Science and Technology, 2015)
To study the robust H∞ infinity control for generalized networked control systems with long time delay, it is assumed that the sensors are clock-driver, and controllers and actuators are event-driver in two sampling periods and limited energy of the external disturbance. The augmented state is used to establish uncertain system model of discrete time-varying, and by using Lyapunov function and linear matrix inequalities,the sufficient conditions for dynamic output H∞ infinity feedback control are found out. A simulation example shows the effectiveness of the method.